"It's like a book in the palm of my hand": Adapting the Safe Delivery App for Papua New Guinea to improve quality of maternal and newborn care. - Delly Babona; Lucy Au; Cherolyn Polomon; Arpita Deb; Hilde Cortier; Disha Agarwalla; John Bolnga; Michaela A Riddell; Angela Kelly-Hanku; Caroline S E Homer; Lisa M Vallely (PLoS ONE)
Background Health workers in many low- and middle-income countries are not adequately trained to provide quality antenatal and intrapartum care. The freely available Safe Delivery App (the App) provides health care professionals with direct and instant access to evidence-based, up-to-date clinical guidelines equipping them with an on-the-job reference guide, even in the most remote areas. In this paper we describe the uptake and acceptability and the process to align the App in Papua New Guinea (PNG). Methods Between June 2022 and December 2024, quantitative and qualitative methods were used to explore the usage and acceptability of the App among health care workers in PNG, re-designing images and aligning clinical content with PNG national clinical guidelines. Dissemination of the App took place through formal and informal networks, including a training of trainers' program in one province. Results The App was seen as an acceptable and useful tool among midwives and nurses working clinically, particularly those in remote areas and midwifery educators. There was an increase in the use of the App, from 354 registered users in 2022 to 1304 in 2024. The majority of users were midwives and nurses, working in primary health care facilities and nursing and midwifery establishments. Participants reported that the App has led to changes in practice, supporting and encouraging staff to follow evidence-based guidelines, improving their clinical management. Conclusion The Safe Delivery App is seen as a useful tool, supporting clinical practice, knowledge and skills, providing users with more confidence in their ability to provide quality maternal and newborn health care. Wider implementation of the App across PNG may be a potential way to support health care workers in the remote settings, providing up to date evidence based clinical guidance in the absence of skilled midwives and doctors.